Conspecific coprophagy stimulates normal development in a germ-free model invertebrate - Jahnes, Benjamin C.; Herrmann, Madeline; Sabree, Zakee L. (PeerJ, 2019)
Microbial assemblages residing within and on animal gastric tissues contribute to various host beneficial processes that include diet accessibility and nutrient provisioning, and we sought to examine the degree to which intergenerational and community-acquired gut bacteria impact development in a tractable germ-free (GF) invertebrate model system. Coprophagy is a common behavior in cockroaches and termites that provides access to both nutrients and the primary means by which juveniles are inoculated with beneficial gut bacteria. This hypothesis was tested in the American cockroach (Periplaneta americana) by interfering with this means of acquiring gut bacteria, which resulted in GF insects that exhibited prolonged growth rates and gut tissue dysmorphias relative to wild-type (WT) P. americana. Conventionalization of GF P. americana via consumption of frass (feces) from conspecifics and siblings reared under non-sterile conditions resulted in colonization of P. americana gut tissues by a diverse microbial community and a significant (p < 0.05) recovery of WT level growth and hindgut tissue development phenotypes. These data suggest that coprophagy is essential for normal gut tissue and organismal development by introducing beneficial gut bacteria to P. americana, and that the GF P. americana model system is a useful system for examining how gut bacteria impact host outcomes.
Keywords: Germ-free insects; Gut microbiome; Development